The Impact of Athletic Brands on Arab Youth Perceptions of Israel: A Review of Sports Diplomacy in Social Science - Maher , Nora (Social Empowerment Journal)
This research offers an Arab view point from the academic fieldwork on the nexus between sports diplomacy and social science. The research examines the impact of sports diplomacy through athletic brands on youth perceptions of Israel in the Arab region. 113 Arab students in four Egyptian and Palestinian Universities were surveyed, through mixed-methods research directed by thematic analysis to examine students’ perceptions of Israel based on the political stance of Arab athletes competing against Israeli athletes at sports mega events. Responses indicate that Arab athletes’ conduct towards Israeli counterparts in the realm of sports diplomacy had a significant impact on students’ perspectives, predominantly fostering unfavorable impressions of Israel. According to the research, there is a gap between youth opinions and the policies of the respective governments. The research concludes that sports boycott is effective in resisting occupation, and that sports and politics are indivisible as the animosity embedded in the Arab-Israeli conflict reflected on respondents’ preferences and emphasized collective national identity among students in the four universities, that linked competition with Israeli athletes to the perception of Israel as enemy. Therefore, the idea of sports normalization appears to be a myth